Pre-Prison and Indigenous Predictors of Institutional Misconduct - Quick, Ellen (International journal of offender therapy and comparative criminology, 2023)
This study prospectively predicted institutional misconduct over a 34-month period using pre-prison factors—intrinsic characteristics an individual brings into prison—stemming from importation theory and indigenous factors—prison environment factors that affect an incarcerated adult—stemming from deprivation theory. Participants were 114 male and female incarcerated adults. Poisson regressions predicting the number of institutional infractions partially supported each of the models tested. Both pre-prison factors of self-regulatory mode and perceived social support were related to infractions but in unique ways. For regulatory mode, locomotion was positively, and assessment negatively associated with misconduct. For social support, perceptions of guidance received within a reliable alliance with others were negatively related to misconduct, whereas perceptions of guidance without that alliance were positively related to institutional misconduct. Of our indigenous factors, sentence length was negatively related to misconduct, whereas custody level was unrelated to misconduct. Implications of the findings and directions for future research are discussed.